Knot numbers used as labels for identifying subject matter of a khipu - Alberto Saez-Rodriguez (Revista Latinoamericana de Etnomatemática, 2013)
This investigation presents a new way to look at the numerical khipu, a knotted-string recording device from Pachacamac (Peru), and the types of information it contains. In addition to celestial coordinates, khipu knots apparently pertain to an early form of double-entry accounting. This study hypothesizes that the khipu sample has the recording capacity needed to register double-entry-like accounts. After the identification of its subject matter, the khipu sample was studied in an attempt to ascertain whether the knot values could represent instructions from the Inca state administration to a local accounting center. The results indicate that the numerical information in the pairing quadrants (determined by the distribution of S- and Z-knots) should be read from top to bottom along the full length of the string and can then provide certain complementary details regarding the projected corn stocks of the Inca stat